Tribological behaviour analysis of hydrogenated and nonhydrogenated DLC lubricated by oils with and without additives. (27th February 2013) - Héau, Christophe; Ould, Choumad; Maurin‐Perrier, Philippe
ABSTRACT Diamond‐like carbon (DLC) is an essential element of friction reduction made major by the desire to reduce energy consumption for environmental and economic reasons. The contribution of the DLC depends on its tribological behaviour. The analysis of the wear of DLC in DLC/steel contact is important because of the high exposure to the wear of coated parts and the low degree of mastery of behaviour of DLC in the lubricants studied and optimised for steel. In this study, we have analysed the tribological behaviour of hydrogenated DLC (a‐C:H) and nonhydrogenated DLC (ta‐C) under various lubrication conditions. Oils with and without additives were used. The results show that the wear of a‐C:H is considerably lower than that of ta‐C in base oils, and in the investigated oil with additives, the wear of ta‐C is substantially reduced. Copyright © 2012 John Wiley & Sons, Ltd.